ChemInform Abstract: Facile Synthesis of Benzo[d]azol‐2(3H)‐ones Using 2‐Phenoxycarbonyl‐4, 5‐dichloropyridazin‐3(2H)‐one as Green CO Source. Issue 2 (23rd December 2015) - Ryu, Ki Eun; Kim, Bo Ram; Sung, Gi Hyeon; Yoon, Hyo Jae; Yoon, Yong‐Jin
Abstract: Using title reagent (II), a number of benzo[d]oxazolones (III), ‐imidazolones (V) and ‐thiazolones (VII) and (IX) are easily prepared from 2‐aminophenols (I), ortho‐phenylenediamines (IV) and 2‐aminothiophenols (VI) and (VIII) in high yields.